The Influence of Human-AI Collaboration and Digital Competence on Generation Z Job Satisfaction - Umban Adi Jaya; Indarta Priyana; Fauzan Manafi Albar; Amna Mawardi; Ade Nurhayati Kusumadewi (Transpublika Publisher, 2026)
The proliferation of digital technology and the preponderance of Generation Z within the occupational sphere are compelling organisations to acclimatise by assimilating artificial intelligence (AI) and augmenting digital proficiency. This inquiry aims to scrutinise the sway of Human-AI Collaboration and Digital Competence upon Job Satisfaction amongst Generation Z cohorts. The investigative paradigm employed is a quantitative disposition utilising survey instrumentation encompassing 100 Generation Z respondents handpicked via purposive sampling. Empirical data were garnered through a questionnaire harnessing a five-tiered Likert gradation and subsequently interrogated via multiple linear regression through SPSS. The culminating findings corroborate that Human-AI Collaboration exerts an affirmative and consequential bearing upon Job Satisfaction, yielding a t-value of 7.156, whilst Digital Competence similarly manifests an affirmative and substantial repercussion with a t-value of 6.403. Concurrently, both exogenous variables wielded a momentous bearing upon Job Satisfaction, producing an F-value of 269.701 at a significance threshold of < 0.001. The coefficient of determination of 0.904 substantiates that 90.4% of the fluctuation in Job Satisfaction is explicable through Human-AI Collaboration and Digital Competence in tandem. These findings suggest that collaboration between humans and AI technology, coupled with high digital competence, can enhance Generation Z’s job satisfaction. Hence, organisations need to optimise the use of AI technology and enhance employees’ digital competence to create a more productive and satisfying work environment.